Problems of Medical Negligence and Its Awareness in India: Understanding Medical Negligence and Legal Duties in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“It is health that is a person’s real wealth and not pieces of gold and silver”.-Mahatma GandhiMedical Negligence is not only a part of Medical Law but it is related to the Health Law too. The components of Medical Negligence as stated by Winfield are Existence of a legal duty, Breach of that legal duty and Damage caused by that breach. For all medical practitioners or doctors it is mandatory to know the legal and judicial aspects related to their profession so that their little awareness can make them more alert and responsible towards their patient. The laws on medical negligence in no manner create any kind of apprehension in the mind of doctors to follow super standards of treatment but these laws expect to follow fair methods of treatment which is required primarily for the treatment of disease in order to do justice to the patient or the sufferer because a person approaches some other person trusting his skills and specialized knowledge. So it is the legal duty of that person to exercise diligence as much as expected from his contemporaries. According to Mahatma Gandhi ‘Patients see God in doctors and in view of Kevin Alan Lee who said that “Being in such a profession where sick, ill and sufferers are your customers who look upon you as the almighty, an absolute amount of care is expected.” Justices Chandramauli K.R. Prasad and V. Gopala Gowda in their decision in the Anuradha Saha case observed that, The patients, irrespective of their social, cultural and economic background, are entitled to be treated with dignity, which not only forms their fundamental right but also their human right, “Hence, it is the duty of doctors to treat their patients with due care and diligence without any malpractices. And if the doctor’s act negligently in that case they can be liable for it according to the Indian laws especially meant to protect rights of victims of medical negligence.